Pengaruh Disiplin Keluarga Kristen Terhadap Tingkah Laku Remaja di Desa Tanjung Medan Kecamatan Tanotombangan Angkola Kabupaten Tapanuli Selatan Tahun 2023 - Selmika Manullang; Goklas J. Manalu; Sandy Ariawan (Sekolah Tinggi Teologi Injili Arastamar (SETIA) Ngabang, 2024)
The aim of this research is to determine the positive and significant influence of Christian Family Discipline on Adolescent Behavior in Tanjung Medan Village, Tanotombangan Angkola District, South Tapanuli Regency in 2023. The research method used is a quantitative research method using descriptive analysis. The population is all teenagers aged 12-15 years in the village of Tanjung Medan, Tanotombangan Angkola District, South Tapanuli Regency in 2023 who are Protestant Christians as many as 65 teenagers and this research is a population study. Data was collected using a positive closed questionnaire with 40 items, namely 20 items for variable Year 2023: 1) Test analysis requirements: a) positive relationship test obtained rxy = 0.571 > rtable(a=0.05,n=65) = 0.244. b) Testing a significant relationship obtained a value of tcount= 5.519 > ttable(a=0.05, dk=n-2=63)= 2.000. 2) Test the effect: a) Test the regression equation, obtained the regression equation Y ̂=